Give me liberty [videorecording (DVD)] - Spencer, Lauren; Galust, Chris; Stoyanov, Maxim (Music Box Films, 2020)
Medical transport driver Vic is late, but it's not his fault. Roads are closed for a protest, and no one else can shuttle his Russian grandfather and emigre friends to a funeral. The new route uproots his scheduled clients, particularly Tracy, a vibrant young woman with ALS. As the day goes from hectic to off-the-rails, their collective ride becomes a hilarious, compassionate, and intersectional portrait of American dreams.